A model describing the rhetorical structure of abstracts of cardiology research articles in english - Angel Rodríguez, Naliet; Bernal Díaz, Pedro Santiago; Rodríguez Ruiz, Mayra (My University, 2021)
Problem to deal with: The Abstract section of the research article (RA) is particularly important because it offers different communicative functions. In the medical field, English has also gained the status of lingua franca since most of the medical journals are published in English and principal contributions in medicine and science are also published in this language. Therefore, it is essential for scientists in the field of medicine to communicate the results of their research in English in order to gain international recognition. Aims: To propose a model describing the rhetorical structure and frequent linguistic elements used in the Abstract section of Cardiology research articles in English Methodology: A mixed-method approach was held in this study. Genre analysis was employed as a methodology for the design of the aforementioned model. A special corpus of ninety research article abstracts from three specialized Cardiology journals was compiled and processed using AntMover 1.10 (2016) and AntConc 3.5.8 Window (2019).  Results and Discussion: The designed model will contribute to improve the academic writing skills of Cuban cardiologists, when writing their research articles abstracts in English, for them to meet the international scientific community demands of their publications.  Conclusions: The findings will make an important contribution to the field of ESP pedagogy as they offer authentic material, which could be used for the teaching and learning of English academic writing.

Problemática: La sección Resumen del artículo de investigación es especialmente importante porque ofrece diferentes funciones comunicativas. En la medicina, el idioma inglés se ha convertido en lingua franca pues la mayoría de las revistas se publican en inglés y las principales contribuciones en la medicina y en la ciencia también son publicadas en ese idioma. Por consiguiente para los científicos en el campo de la medicina es esencial la comunicación de sus resultados investigativos en idioma inglés para poder alcanzar reconocimiento internacional.  Objetivo(s): Proponer un modelo que describa la estructura retórica y los elementos lingüísticos más frecuentemente utilizados en la sección Resumen de los artículos de investigación en inglés, en la especialidad de Cardiología
Modelo para describir la estructura del resumen del artículo de investigación de cardiología en inglés
Keywords: Genre Analysis; Research Article Abstract; Discourse Community; Análisis de Género; Artículo de Investigación; Comunidad Discursiva; Lengua Inglesa; Cardiología; Ciencias Médicas; Lingüística